Implementation of competency based curriculum in pre-service nursing education: Middle range theory - Claudine Muraraneza; Gloria Ntombifikile Mtshali (Elsevier, 2018)
Background: Competency Based Curriculum is acknowledged as the benchmark for transforming and up scaling the education and training of the health workforce for improved population and health outcomes. It was adopted in pre-service nursing education in Rwanda in 2007, when it switched from a content-driven curriculum to align education with the demands of the working environment. Although this approach is recommended in national health policies, there is no clear guide for its implementation at the nursing school level. Aim: To develop a middle range theory that guides the practice of competency based curriculum in pre-service nursing education. Method: The grounded theory of Corbin and Strauss was followed. After obtaining ethical approval, data was collected through individual interviews with the staff and focus group interviews with the students that were triangulated by observations and document analysis. Results: Two main categories emerged: (a) Process of implementing Competency based curriculum which generated two sub-categories: (1) Implementation, (2) monitoring and evaluation; (b) outcome based education generated three subcategories: (1) health care system, (2) graduates, and (3) nursing education system. Discussion: In this context, competency based curriculum entails the processes used to achieve learning outcomes. These processes student-centered implementation, and monitoring and evaluation that result in the accreditation of curriculum at the end of the cycle. The outcomes of these processes lead to the production of competent graduates qualified as agent of change, lifelong students and independent practitioners. Conclusion: A middle range theory serves as a guide to implement competency based curriculum in pre-service nursing education. Keywords: Competency based curriculum, Pre-service education, Nursing, Middle range theory, Rwanda